Single-molecule FRET reveals the energy landscape of the full-length SAM-I riboswitch - Manz, Christoph; Samanta, Ayan; Jäschke, Andres; Nienhaus, G. Ulrich (Nature chemical biology, 2017)
S-adenosyl-L-methionine (SAM) ligand binding induces major structural changes in SAM-I riboswitches, through which gene expression is regulated via transcription termination. Little is known about the conformations and motions governing the function of the full-length Bacillus subtilis yitJ SAM-I riboswitch. Therefore, we have explored its conformational energy landscape as a function of Mg2+ and SAM ligand concentrations using single-molecule Förster resonance energy transfer (smFRET) microscopy and hidden Markov modeling analysis. We resolved four conformational states both in the presence and the absence of SAM and determined their Mg2+-dependent fractional populations and conformational dynamics, including state lifetimes, interconversion rate coefficients and equilibration timescales. Riboswitches with terminator and antiterminator folds coexist, and SAM binding only gradually shifts the populations toward terminator states. We observed a pronounced acceleration of conformational transitions upon SAM binding, which may be crucial for off-switching during the brief decision window before expression of the downstream gene.